Light-induced degradation of fullerenes in organic solar cells: a case study on TQ1:PC71BM. Issue 25 (7th June 2018) - Wang, Yuming; Jafari, Mohammad Javad; Wang, Nana; Qian, Deping; Zhang, Fengling; Ederth, Thomas; Moons, Ellen; Wang, Jianpu; Inganäs, Olle; Huang, Wei; Gao, Feng
Abstract : The stability of organic solar cells (OSCs) is critical for practical applications of this emerging technology. Abstract : The stability of organic solar cells (OSCs) is critical for practical applications of this emerging technology. Unfortunately, in spite of intensive investigations, the degradation mechanisms in OSCs have not been clearly understood yet. In this report, we employ a range of spectroscopic and transport measurements, coupled with drift-diffusion modelling, to investigate the light-induced degradation mechanisms of fullerene-based OSCs. We find that trap states formed in the fullerene phase under illumination play a critical role in the degradation of the open-circuit voltage ( V OC ) in OSCs. Our results indicate that the degradation is intrinsic to the fullerenes in OSCs and that alternative acceptor materials are desired for the development of stable OSCs.